Anak usia sekolah, Pengetahuan, GAMBARAN TINGKAT PENGETAHUAN DAN PERSEPSI ANAK USIA SEKOLAH TENTANG PERILAKU MEROKOK - Rahma rahma (Jurnal Medika Hutama, 2021)
Smoking prevalence has increased not only among adults but also among adolescents and schoolchildren. Schoolchildren perceive smoking as something prevailing as a result of lack of knowledge about the dangerous health effects of smoking cigarettes. The study was aimed at assessing levels of schoolchildren’s knowledge and perceptions about smoking behavior. This quantitative study was conducted using descriptive approach. The population of the study was schoolchildren, with 188 participants taking part as samples which were determined using simple random sampling. The data were collected using questionnaire and then analyzed using frequency distribution method. The study found that 97.3% of participants had poor knowledge about smoking, 52.7% had positive perception about smoking behavior, and 14 schoolchildren smoked outside and out of school hours. It is suggested that health workers improve promotional and preventive measures as parts of the strategy to prevent the rise of new smokers among schoolchildren. Keywords : Schoolchildren, Knowledge, Perceptions, Smoking behavior